ANTIBACTERIAL EFFECTS OF BLACK QUICK (Nigella sativa L.) OIL EMULGEL AGAINST Streptococcus mutans (IN VITRO) - Irma Dewi Ratnawati; Linda Septiana; Alrevo Panji Auradewa (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Secondary infection of traumatic ulcer can be caused by Streptococcus mutans. Black seed oil emulgel (Nigella sativa L.) has a saponin that has antibacterial effect on Streptococcus mutans growth. The purpose of this research for know the antibacterial effect of black seed oil emulgel (Nigella sativa L.) on Streptococcus mutans growth in vitro.Method: Experimental laboratory in vitro was held using post-test only control group design. There are four groups: negative control group and black seed oil emulgel in 5%, 7%, and 10%. Disk diffusion method was used in this research. Data analyzed by Anova test.Result: The result indicates some significant effect of black seed oil emulgel on Streptococcus mutans growth from Anova test 0,000(<0,05).Conclusion: It can be concluded that there is antibacterial effect on black seed oil emulgel to Streptococcus mutans growth.